PENGHAYATAN SEMANGAT PELAYANAN SOSIAL DAN ROHANI FRANK DUFF BAGI ANGGOTA LEGIO MARIA - Fitri, Crisensia; Laksito, Petrus Canisius Edi (CREDENDUM: Jurnal Pendidikan Agama, 2025)
The research data was collected by using an individual interview approach, then research data analysis done by using an inductive approach. The results of the study indicate that the informants perceive the Legion of Mary as a group of Catholics who are always devoted and pray to Mother Mary regularly in order to develop and strengthen their faith in Jesus. The spirituality of the Legion of Mary lies in the spirit of prayer and devotion to Mother Mary as the Mother of Jesus and the obedient of Mary to God's will. The spirituality of the Legion of Mary is expressed through regular prayer activities as well as social and humanitarian service activities done by the legionaries.